Patient Safety from a Different Perspective: An Evaluation of the Type of Foods and Drinks Visitors Bring for Postoperative Patients - Seher Ünver; Zeynep Kızılcık Özkan; Hatice Merve Alptekin; Sacide Yıldızeli Topçu (Patient Safety and Quality Improvement Journal, 2016)
Introduction: To introduce different types of foods and beverages visitors bring for postoperative patients. Materials and Methods: This descriptive study was conducted on 96 visitors of postoperative patients at Trakya University Hospital in Edirne, Turkey. Data were collected in face-to-face interviews (15 min) during visiting hours (02:00-04:00 p.m.) between August and September, 2015. The  questionnaire included 15 questions on demographic characteristics, patient/visitor relation, visitor's knowledge of the type of patient's surgery, date of surgery, and the onset of patient's oral intake, the selected foods and/or drinks, and cause of such selection. Results: Based on the findings, 72.9% of the visitors had brought food for the patients, and soup was the most frequently selected food type (25.7%); also, 41.4% of the visitors had brought the food the patient had requested. In total, 74% of the visitors had brought drinks, with fruit juice accounting for 63.4% of the selected beverages; also, 53.5% of the visitors had brought the drink the patient had requested. By comparing the type of foods and drinks with the type and date of surgery, it was revealed that some visitors had brought pastries and biscuits for patients undergoing gastrectomy on the first postoperative day. Conclusion: It is recommended to control and manage the type of food products visitors bring for the patients during visiting hours. Moreover, visitors should be instructed on how to select foods or drinks for the patients.